The Strategic Role of Information Professionals in Advancing Digital Transformation in Educational Institutions - Akhmed Reza Fachlevi; Kautsar Eka Wardhana; Muhammad Solekhin (Journal of Educational Management Research, 2025)
Digital transformation in the education sector has become an inevitable challenge alongside rapid advancements in information technology. This study aims to examine the strategic role of information professionals in supporting digital transformation within educational institutions. Using a qualitative approach supported by a comprehensive literature review, the study analyzes how these professionals contribute to planning, implementing, and sustaining digital initiatives. The findings indicate several key barriers, including limited budgets, resistance to change, skill gaps, and inadequate technological infrastructure. Despite these constraints, information professionals play a critical role as change agents who drive innovation, enhance administrative efficiency, and strengthen the alignment between digital solutions and institutional goals. The study implies that developing professional competencies, improving digital literacy among stakeholders, and fostering stronger collaboration between information personnel and institutional leaders are essential strategies for achieving sustainable digital transformation in education. This research contributes to a deeper understanding of human resource readiness in digital initiatives and offers practical insights for policymakers and educational administrators.